Qualidade sanitária e fisiológica de sementes de trigo produzidos na fronteira oeste/RS - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The internal demand for wheat is greater than Brazilian production, demonstrating the need to adopt cultivation management practices that, in turn, promote the production of high quality seeds to favor the adequate establishment and development of crops in the field, aiming to cover to market needs in quantity and quality. In this sense, the objective of the present work was to evaluate the incidence of pathogens in wheat seeds and their influence on the physiological quality of the seeds. The experiment was carried out at the Phytopathology and Soil Microbiology Laboratory and at the Seeds Laboratory of the Federal University of Pampa – Campus Itaqui. For germination and health tests, seeds from ten wheat cultivars TBIO CALIBRE, ORS SOBERANO, TBIO TRUNFO, TBIO CAPAZ, TBIO AUDAZ, TBIO PONTEIRO, TBIO ASTRO, ORS ABSOLUTO, ORS FEROZ, TBIO MOTRIZ were used. The wheat seeds were produced in 2023, on a rural property located in the municipality of Maçambará RS. The experimental design was completely randomized (DIC) with ten treatments and four replications. Seed health and physiological quality tests were evaluated, where for quality analysis the health tests were evaluated using the blotter test method in which 25 seeds were placed under three layers of germination paper moistened with sterilized distilled water in Gerbox type boxes. The seeds were incubated in BOD for 24h at 20 ± 2 °C. After this period, the seeds were frozen at -20 °C for 24 hours and returned and placed again in BOD at 20 ± 2 °C for another five days. The seeds were analyzed individually under a stereomicroscope where the occurrence of fruiting typical of fungal growth was assessed. For the vigor and germination test, 50 seeds were distributed on the germination paper, and placed in the germinator at a temperature of 20 °C, for four days to evaluate the vigor test and eight days for the germination test. In the 1st count, the number of germinated seeds was evaluated and in the 2nd count, germinated, non-germinated, abnormal, contaminated seeds, aerial part length, root part length, fresh mass and dry mass were evaluated. The data obtained were subjected to analysis of variance, and the means were compared using the Scott-Knott test (P≤0.05) in the statistical software SISVAR DEX UFLA (FERREIRA, 2011). The main fungi found in the seed health test were: Alternaria alternata, Bipolaris sp., Fusarium sp. and Pyricularia oryzae. The TBIO ASTRO cultivar presented a lower incidence of pathogens and the TBIO ASTRO AND OR FEROZ cultivars presented better physiological parameters. The importance of carrying out more studies in the area is also highlighted, in order to promote constant updates and advances in crop management.
Sanitary and physiological quality of wheat seeds produced in the western border/RS
Keywords: Triticum aestivum L.; Germinação; Patógenos de sementes; Vigor; Germination; Seed pathogens; CNPQ::CIENCIAS AGRARIAS